Survey for legume and cereal viruses in Iraq - El-Muadhidi, Muthana A.; Jerjess, Myasser; Makkouk, Safaa G.; Murad, Salou (Phytopathologia Mediterranea, 2001)
A survey was conducted in April 2000 to identify virus diseases affecting legume (chickpea, faba bean andlentil) and cereal (wheat and barley) crops at different locations in Iraq (Baghdad, Al-Anbar, Diyala, At-Tamim andNinawa governorates). The survey covered 54 randomly selected legume fields (36 faba bean, 8 chickpea, and 10lentil) and 23 cereal fields (18 wheat and 5 barley). All viruses were identified and their incidence determined bylaboratory testing 100–200 randomly collected samples and 20–25 symptomatic samples from each field. A total of7663 legume and 3455 cereal samples was collected and tested for 12 legume and 5 cereal viruses by tissue blotimmunoassay (TBIA). In faba bean fields, Bean yellow mosaic virus (BYMV, genus Potyvirus, family Potyviridae) wasthe most common, followed by Bean leaf roll virus (BLRV, family Luteoviridae). In the 18 most extensively infectedfaba bean fields (more than 50%), total virus incidence ranged from 80 to 100%, and BYMV was by far the mostcommon. Other viruses that were detected in legumes at low incidence were: Alfalfa mosaic virus (AlMV, genusAlfamovirus, family Bromoviridae), Faba bean necrotic yellows virus (FBNYV, genus Nanovirus), Cucumber mosaicvirus (CMV, genus Cucumovirus, family Bromoviridae), Broad bean wilt virus (BBWV, genus Fabavirus, familyComoviridae), Beet western yellows virus (BWYV, genus Polerovirus, family Luteoviridae) and Chickpea chloroticdwarf virus (CpCDV, genus Mastervirus, family Geminiviridae). This is the first report of FBNYV, BWYV and CpCDVinfecting legumes in Iraq. In the cereal fields, Barley yellow dwarf virus-PAV (BYDV-PAV, genus Luteovirus, familyLuteoviridae) was detected in about 1% of random samples. Virus disease incidence in all cereal fields based on fieldobservations was less than 5%. Other viruses were rarely detected in cereals: BYDV-MAV (genus Luteovirus, familyLuteoviridae) and Cereal yellow dwarf virus-RPV (CYDV-RPV, genus Polerovirus, family Luteoviridae).